Dampak Keterampilan Proses Sains Terhadap Literasi Sains - Nurul Husna; A. Halim; Evendi Evendi; M Syukri; Syahrun Nur; Elisa Elisa; Ibnu Khaldun (Postgraduate, University of Mataram, 2022)
The purpose of this study was to determine the difference in the increase in scientific literacy skills of students who were taught with a science process skills approach with those taught using a direct learning model in physics learning. This study uses a quantitative approach to the Non-Equivalent Control Group Design experiment. The population used in this study were students of class XI MIA with a sample of 60 people taken by random sampling. The instrument used in this study was a test question in the form of an essay. The data of this study were analyzed using the average test, N-gain and independent sample t-test. The results showed that the average value of scientific literacy in the experimental class was in the high category and the control class in the medium category. In addition, based on the independent sample t-test, it was found that there was a significant difference in the increase in students' scientific literacy skills. So, it can be concluded that there is a difference in the improvement of students' scientific literacy skills in learning Physics taught with a science process skills approach with those taught using a direct learning model.